GIANT CELL TUMOUR OF THE SACRUM: FUNCTION-PRESERVING SURGERY WITH EXTENDED CURETTAGE AND ILIO-LUMBAR FUSION - Lakdawala, Riaz H.; Ahmad, Tashfeen; Enam, Syed A. (Journal of Ayub Medical College Abbottabad, 2013)
Giant cell tumours of the sacrum pose a unique therapeutic challenge due to the inaccessibility of the tumour, significant intra-operative blood loss from extensive vascularity, high rate of local recurrence with conservative surgery, and loss of neurological function and mechanical instability with en-bloc excision. We present a case where successful outcome was achieved by tailoring treatment in consideration of the above issues. A 28 year old male diagnosed on biopsy to have giant cell tumour of the sacrum presented to us with low-back pain, left-sided S1 radiculopathy, ankle weakness and urinary incontinence. MRI showed a tumour involving the S1 and S2 vertebral segments, breaching the posterior cortex and compressing the neural elements. An angiographic tumour embolization was performed followed by surgery through a posterior approach whereby an extended curettage was done, carefully freeing the sacral nerve roots and abrading the bone using high-speed burr. An ilio-sacro-lumbar fusion was done employing ilio-lumbar instrumentation and bone grafting. Post-operatively, within a week the patient was ambulated with a lumbar corset. At 9 months follow-up, the patient was completely pain free, had no ankle weakness, and had normal continence. This treatment approach resulted in preservation of neurologic function and maintenance of spinal stability, thus the patient returned to full function. Keyword: Giant cell tumour of bone; sacrum; selective arterial embolization; extended curettage; ilio-lumbar fusion; segmental instrumentation.